Współczesna kobiecość i męskość w opiniach młodych dorosłych – analiza w kontekście stereotypów płci oraz własnych koncepcji tożsamości płciowych badanych. - Dobosz, Dagmara (Studia Edukacyjne, 2022)
The analysis of the characteristics that society considers to be characteristic of each gender is one of the oldest perspectives in the study of gender stereotypes. Bearing in mind the changes taking place in the lifestyles of modern women and men as well as the fact that each era creates its own specific image of femininity and masculinity, the respondents (N = 450) were asked about what they consider to be the characteristic features of modern women and men. In addition, they were asked to identify the characteristics that best describe them. Analysis of the responses showed that the respondents attributed to modern women characteristics indicating the stereotype of a career-focused woman, while in the case of the male respondents, the indicated attributes of a modern woman, were a combination of the stereotype of a female sex object and a businesswoman. In the opinions of both groups of respondents, the masculinity is based on the characteristics traditionally attributed to men, gently expanded characteristics of the stereotype of a man, i.e. a life partner who is involved in family life. The question about self-perception in terms of femininity and masculinity showed that the vast majority of women surveyed described themselves using traits considered as typically masculine or combining masculine and feminine traits. In contrast, when describing themselves, men chose traits characteristic of traditional masculinity, while traits associated with femininity (e.g., caring) were only supplementary.